KNOWLEDGE ABOUT IRON DEFICIENCY ANEMIA AMONG PREGNANT MOTHERS IN THE FIRST TRIMESTER IN SRI LANKA (Proceedings of the Global Public Health Conference, 2019)
The Hemoglobin (Hb) concentration below 11g/dl during pregnancy leads to Iron Deficiency Anemia (IDA).  As increased maternal iron needs and demands from the growing fetus and placenta, pregnant mothers are at risk of having IDA which causes many complications during pregnancy and infancy. The purpose of this study is to explore the knowledge about IDA of pregnant mothers in the first trimester. A self-administered questionnaire was distributed in this quantitative descriptive study among 180 pregnant mothers in the first trimester using convenience sampling method, at the antenatal clinics, District General Hospital, Matara. Ethical approval was obtained from the Ethics Review Committee of the National Hospital of Sri Lanka. Data was analyzed by descriptive statistics using SPSS 22 version. Significantly 80% of the respondents have identified low Hb level (
Keywords: First trimester; iron deficiency anemia; knowledge; pregnant mothers; Sri Lanka